OPTIMASI IDENTIFIKASI BORAKS MENGGUNAKAN PEREAKSI DIETILDITIOKARBAMAT SECARA SPEKTROFOTOMETRI UV-Vis - Armon Fernando (Jurnal Penelitian Farmasi Indonesia, 2015)
Identification of optimization studies have been conducted borax in grilled meatballs with diethyldithiocarbamate reagent (DEDTC) and detected byUV-Vis spectrophotometer. Samples containing borax in the furnace at a temperature of 600 ⁰C for ± 3 hours and treated with a solution of 10%diethyldithiocarbamate in NaOH 0.2 N. The results derivatization diethyldithiocarbamate borax with 2 ml of 10% at a temperature of 40 ⁰C or 60 minto detect a wavelength of 422 nm. Boron-diethyldithiocarbamate complex produced more stable in methanol and yellow